Tata Kelola Manajemen Administrasi Pada Kelompok Tani Hutan (KTH) Tani Makmur Tulungagung - Satriyono, Gandung; Rukmini, Meme; Eferyn, Krissantina; Alfiona, Fanisa Norma; Utama, Muhammad Bandung Budi (STIE Malangkucecwara, 2025)
This community service activity aims to enhance the administrative management skills of the members of the Forest Farmers Group (KTH) Tani Makmur in Tulungagung. The limited understanding of administrative management among members has hindered the group’s ability to operate in an orderly and accountable manner. The implementation method included preparation, socialization, training, and mentoring stages using a participatory approach. The program provided training on archiving, report preparation, and organizational document management. The results showed significant improvements in participants’ knowledge and skills in administrative management, the establishment of a more organized record-keeping system, and the development of awareness regarding transparency and institutional accountability. The main output of this activity is an administrative management guidebook that can serve as a practical reference for the group. Overall, this activity positively impacted institutional strengthening and professionalism within the farmers’ organization.